PENGEMBANGAN MEDIA PEMBELAJARAN AUGMENTED REALITY (AR) BERBASIS TPACK PADA MATERI SISTEM EKSKRESI MANUSIA DALAM PEMBELAJARAN BIOLOGI SMA - Kinanti Natasha; Yenny Anwar; Kodri Madang (Biosfer: Jurnal Pendidikan Biologi, 2026)
This study aimed to develop Technological Pedagogical Content Knowledge (TPACK)-based Augmented Reality (AR) learning media on the topic of the human excretory system for high school students. The research was conducted from October to December 2024 at a sample high school in Palembang and the Biology Education Laboratory of Sriwijaya University. The research method used the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation), reported up to the small group trial stage. Media validation was carried out by a material expert and a media expert, while practicality testing involved 30 students and 1 biology teacher. Validation results showed content validity of 81.7% (very valid) and media design validity of 92.5% (very valid). The small group trial revealed practicality scores of 95.2% from students and 100% from the teacher. Student learning evaluation results indicated that all students scored above 80 after using the media, demonstrating its effectiveness in enhancing conceptual understanding of the excretory system. In conclusion, the TPACK-based AR learning media developed is valid, practical, and effective for improving biology learning on the human excretory system topic.